2011
DOI: 10.3844/jcssp.2011.1003.1010
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties of Standard Arabic Phonemes Spoken by Non-Arab Primary School Children based on Formant Frequencies

Abstract: Problem statement:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…For future work, more than one of the represented features of Arabic speech such as: spectral envelope, onsets representation and formant frequencies can be tested separately and/or combined for accomplishing the process of segmentation [10]. Also, more constraints can be added to Peak picking to enhance the algorithm.…”
Section: Future Workmentioning
confidence: 99%
“…For future work, more than one of the represented features of Arabic speech such as: spectral envelope, onsets representation and formant frequencies can be tested separately and/or combined for accomplishing the process of segmentation [10]. Also, more constraints can be added to Peak picking to enhance the algorithm.…”
Section: Future Workmentioning
confidence: 99%
“…From the spectrogram, the formants (F 1 , F 2 , F 3 and F 4 ) were studied and samples which fall in the average formants values were extracted. [19][20] These frequencies were obtained as in (3).…”
Section: Data Processingmentioning
confidence: 99%
“…These phonemes of letters have closely articulated phonemes and similar sound with the Malay language, but in fact, have different articulation points. Meanwhile, [27] have reported that, there are seven consonants (/q/-[‫,]ق‬ ‫,]ظ[-/∂/‬ /x/-[‫,]خ‬ /γ/-[‫,]غ‬ /H/-[‫,]ح‬ ‫]ع[-/?/‬ and /h/-[‫,)]ه‬ unable to give the promising results based on inappropriate values of formant frequencies measured using spectrogram. Thus, it is considered as difficult Arabic consonants to be articulated properly among Malaysian primary school students.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is considered as difficult Arabic consonants to be articulated properly among Malaysian primary school students. Experts and researchers had identified those phonemes after years of teaching the Malay students from all levels of educations [5], [8], [9], [27], and those misarticulate phonemes have been summarized in Table 1. Malaysian Journal of Computer Science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation